DYNAMICS OF THE ECONOMIC AND SOCIAL LIFE OF MARINE PARTS DUANO IN VILLAGE CAPE RED SAND LAND DISTRICT DISTRICT INDRAGIRI HILIR YEAR 2006-2012 - Vevianti, Dessi Eldo Vevianti Eldo; Ibrahim, Bedriati Ibrahim Bedriati; Melay, Ridwan Melay Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The dynamics or changes affecting the socio-economic life of the people of Indonesia, as well as perceived by Duano tribe in the village of Tanjung Pasir Indragiri Hilir district, in terms of social change in the social structure and change values in terms of culture, whereas in the economic life of change livelihoods and increasing types of livelihood. The purpose of this study was to determine (1) Determine the cause of the sea tribe (Duano) could not leave Menongkah (2) Knowing the factors that led to the sea tribe (Duano) willing to accept change (3) To know the dynamics of the Sea Tribe Economic Social Life (Duano) in Tanjung Pasir Tanah Merah Indragiri Hilir Year 2006-2012. The method used is the method of Qualitative and Quantitative. Engineering samples used in this research is purposive sampling technique. Data analysis techniques in this research is descriptive-qualitative. The results of this study are the socio-economic life of the tribe Duano sea experience or fluctuating dynamics are ups and downs of life are always changing, the Duano sea tribe in the village of Tanjung Pasir has undergone a change in the socio-economic field. In the social emphasis on education and health sector, the education sector Duano people have realized the importance of education for their children, while in the health sector they have switched went to the doctor and paramedics. If in economics focused on livelihoods and incomes, the livelihoods they have had livelihood out of their habit during this time that menongkah, despite that they remain menongkah because it is a tradition handed down them since time immemorial. While in their income sector has had more income than before because they have had a good livelihood and have been able to organize their finance.Keywords: Dynamics of, Economic and Social, Life Sea Tribe Duano